Synthesis, optical, and photocatalytic properties of cellulose-derived carbon quantum dots - Shabnam Sheshmani; Mahan Mardali; Soheila Shokrollahzadeh; Yasamin Bide; Roya Tarlani (Scientific Reports)
Abstract Carbon quantum dots (CQDs) represent a novel class of zero-dimensional nanomaterials with exceptional optical and photocatalytic properties. This study investigates the hydrothermal synthesis of cellulose-derived CQDs, aiming to evaluate their effectiveness in degrading industrial dyes. The synthesized CQDs exhibited a quasi-spherical morphology averaging 7 nm in diameter and a band gap of 4 eV, characterized using Fourier Transform Infrared (FT-IR), Raman spectroscopy, X-ray diffraction (XRD), and high-resolution transmission electron microscopy (HR-TEM). Under optimized conditions of pH 4 and a CQD concentration of 0.04 g, the CQDs achieved notable degradation efficiencies of 84.81% for Acid Dye 5R.113 and 55.4% for Reactive Dye TB133 after 120 min of UV irradiation. The superior photocatalytic performance is attributed to the synergistic effects of optimized particle size (enabling strong quantum confinement), abundant surface functional groups (promoting effective interaction with dye molecules), and enhanced light absorption capabilities (boosting photogenerated charge carrier production). Kinetic studies revealed a pseudo-second-order degradation model, with correlation coefficients nearing 0.99, indicating complex interactions between dye molecules and CQD surfaces. The study underscores the potential of using cellulose—a renewable and abundant biopolymer—as a sustainable precursor for eco-friendly photocatalytic systems. This research provides compelling evidence for the application of cellulose-derived CQDs in addressing industrial wastewater treatment challenges through efficient and safe degradation of persistent organic pollutants.